Preparatory suppression and facilitation of voluntary and involuntary responses to loud acoustic stimuli in an anticipatory timing task - Nguyen, An; Jacobs, L.A.; Tresilian, J.R.; Lipp, Ottmar; Marinovic, Welber (WILEY, 2021)
In this study, we sought to characterize the effects of intense sensory stimulation on voluntary and involuntary behaviors at different stages of preparation for an anticipated action. We presented unexpected loud acoustic stimuli (LAS) at-rest and at three critical times during active movement preparation (−1,192, −392, and 0 ms relative to expected voluntary movement onset) to probe the state of the nervous system, and measured their effect on voluntary and involuntary motor actions (finger-press and eye-blink startle reflex, respectively). Voluntary responses were facilitated by LAS presented during active preparation, leading to earlier and more forceful responses compared to control and LAS at-rest. Notably, voluntary responses were significantly facilitated on trials where the LAS was presented early during preparation (−1,192 ms). Eye-blink reflexes to the LAS at −392 ms were significantly reduced and delayed compared to blinks elicited at other time-points, indicating suppression of sub-cortical excitability. However, voluntary responses on these trials were still facilitated by the LAS. The results provide insight into the mechanisms involved in preparing anticipatory actions. Induced activation can persist in the nervous system and can modulate subsequent actions for a longer time-period than previously thought, highlighting that movement preparation is a continuously evolving process that is susceptible to external influence throughout the preparation period. Suppression of sub-cortical excitability shortly before movement onset is consistent with previous work showing corticospinal suppression which may be a necessary step before the execution of any voluntary response.